Incidence and cost of intraoperative waste of hip and knee arthroplasty implants - Zywiel, Michael; Ulrich, Slif D.; Höppchen, Arnold; Duncan, James L.; McGrath, Mike S.; Mont, Michael A. (The journal of arthroplasty, 2010)
Many strategies have been reported for decreasing the cost of orthopedic procedures, but prosthetic waste has not been investigated. The purpose of this study was to characterize the cost of intraoperative waste of hip and knee implants. A regional prospective assessment was performed, evaluating the reasons for component waste, the cost of the wasted implants, and where the cost was absorbed (hospital or manufacturer). Implant waste occurred in 79 (2%) of 3443 procedures, with the surgeon and operating room staff bearing primary responsibility in 73% of occurrences. The annualized cost was $109 295.35, with 67% absorbed by hospitals. When extrapolated to the whole of the United States, the annual cost to hospitals would be $36 019 000 and is estimated to rise to $112 033 000 by 2030, representing a potential target for educational programs and other cost containment measures.